Konsumsi Kecernaan Bahan Kering dan Bahan Organik Ternak Babi Fase Starter yang diberi Tepung Daun Katuk dan Tepung Kunyit serta Kombinasinya - Nuba, Yohanes; Sembiring, Sabarta; Amalo, Daud (Yayasan Sumber Daya Manusia Cerdas, 2024)
The purpose of this research was to determine the effect of supplementation of katuk leaf flour (Sauropus androgynus L. Merr) and turmeric flour (Curcuma domestica) and their combination in rations on the consumption and digestibility of BK and BO of start-phase landrace pigs. The material used was 12 landrace breed pigs aged 1-2 months with an initial body weight range of 6-14 kg with an average of 10.25k kg Coefficient of Variance (CV = 20%). The experimental research method used a randomized group design with 4 treatments and 3 repeats. The treatment tried was R0: basal ration without supplemented katuk leaf flour and turmeric flour, R1: basal ration supplemented 4% katuk leaf flour, R2: basal ration supplemented 1% turmeric flour, R3: basal ration supplemented 4% katuk leaf flour + 1% turmeric flour. The variables studied are consumption, digestibility of dry matter and organic matter. The data obtained were analyzed using variety analysis. The results of this study showed that dry matter consumption (g/h/d) R0: 1097.77; R1: 1212,72; R2: 1124.41; R3: 1246.14, organic matter consumption (g/h/d) R0: 935.51; R1: 1032.39; R2: 956.19; R3: 1071.48, dry matter digestibility (%)R0: 60,88; R1: 64,76; R2: 62,79; R3: 66,and digestibility of organic matter (%) R0: 61,49; R1: 65,44; R2: 63,73; R3: 67,33. The results of the variety analysis showed that the treatment had no real effect (P>0.05) on the consumption and digestibility of BK and BO. It was concluded that supplementation of 4% katuk leaf meal and 1% turmeric flour and their combination in the basal ration provided the same consumption and digestibility of dry matter and organic matter as the basal ration without supplementation of katuk leaf meal and turmeric flour and their combination in start-phase landrace pigs.